PEMBERANTASAN TINDAK PIDANA KORUPSI DAN DIMENSI SISTEMATIK HUKUM KHUSUS - Nopsianus Max Damping (to-ra, 2019)
Abstract The legal politics of eradicating corruption in Indonesia has long been applied. This can be traced through a track record that begins with enforcement corruption eradication regulations around 1950, even then still in a limited scope, but at least in it has begun awareness arises about the importance of efforts to eradicate corruption. This article tried to argue even though, Corruption in Indonesia has taken place systematically and is widespread so that it not only harms the country's finances, but also has violated the social and economic rights of the community at large, the eradication of corruption needs to be done in extraordinary ways. Thus, the eradication of corruption must be done in a special way inline with Law No. 31 of 1999 concerning Eradication of Corruption Crime. Keywords: eradication of corruption, systematic dimension, special law